谓词公式("x)F(x) Þ ("x)G(x)的前束范式是( )
A: ("x)("y) (F(x) Þ G(y))
B: ($x)("y)(F(x) Þ G(y))
C: ("x)($y) (F(x) Þ G(y))
D: ($x)($y)(F(x) Þ G(y))
A: ("x)("y) (F(x) Þ G(y))
B: ($x)("y)(F(x) Þ G(y))
C: ("x)($y) (F(x) Þ G(y))
D: ($x)($y)(F(x) Þ G(y))
B
举一反三
- 谓词公式($x)F(x) Þ ($x)G(x)的前束范式是( )。 A: ("x)("y) (F(x) Þ G(y)) B: ($x)("y)(F(x) Þ G(y)) C: ("x)($y) (F(x) Þ G(y)) D: ($x)($y)(F(x) Þ G(y))
- 以下哪项是前束范式 A: "x"y(F(x) ÙF(y) ®G(y,x)) B: "x (F(x) Ù$y(F(y) ®G(y,x))) C: "x (F(x) Ù F(y) ®$y G(y,x)) D: "x (F(x) Ù "y F(y) ® G(y,x))
- Ø"xF(x)® $yG(y)的前束范式是( ) A: "x$y(Ø F(x) ® G(y)) B: "x"y(Ø F(x) ® G(y)) C: $x"y(Ø F(x) ® G(y)) D: $x$y(Ø F(x) ® G(y))
- 公式“∀xF(x)→∃yG(x,y)”的前束范式是 A: ∃x∃y(F(x)→G(z,y)) B: ∀x∃y(F(x)→G(z,y)) C: ∃x∀y(F(x)→G(z,y)) D: ∀x∀y(F(x)→G(z,y))
- "x F(x,y) → ¬ $y G(x,y)的前束范式 A: $x$y(F(x,m) ®Ø G(t,y)) B: $x∀y(F(x,m) ®Ø G(t,y)) C: ∀x$y(F(x,m) ®Ø G(t,y)) D: ∀x$y(F(x,m) ® ØG(t,y))
内容
- 0
以下哪个不是谓词公式? A: F(x) B: F(x)ØÚG(x,y) C: "x(F(x)®G(x)) D: $x"y(F(x)®G(y)ÙL(x,y))
- 1
以下哪个不是谓词公式? A: F(x) B: F(x)ØÚG(x,y) C: "x(F(x)®G(x)) D: $x"y(F(x)®G(y)ÙL(x,y))
- 2
在谓词公式("x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x,y,z))中,("x)的辖域是() A: (F(x)ÞG(y)) B: F(x) C: (F(x)ÞG(y))Þ($y)(H(x)∧L(x,y,z)) D: ("x)(F(x)
- 3
公式(∀xF(x,y)→∃yG(y))→∀xH(x,y)的前束范式是() A: ∀x∀t∀w((F(x,y)→G(t))→H(w,y)) B: ∀x∃t∀w((F(x,y)→G(t))→H(w,y)) C: ∀x∃y((F(x,y)→G(y))→H(x,y)) D: ∃x∃t∃w((F(x,y)→G(t))→H(w,y))
- 4
在谓词公式("x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z))中,("x)的辖域是( ) A: (F(x)ÞG(y)) B: F(x) C: (F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z)) D: ("x)(F(x)